2015
DOI: 10.1038/onc.2015.188
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin induction abrogates the BRAF inhibitor response of BRAF V600E/PTEN-null melanoma cells

Abstract: The mechanisms by which some melanoma cells adapt to BRAF inhibitor therapy are incompletely understood. In the present study, we used mass spectrometry-based phosphoproteomics to determine how BRAF inhibition remodeled the signaling network of melanoma cell lines that were BRAF-mutant and PTEN-null. Short-term BRAF inhibition was associated with marked changes in fibronectin-based adhesion signaling that were PTEN-dependent. These effects were recapitulated through BRAF siRNA knockdown and following treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 50 publications
5
77
0
Order By: Relevance
“…Shared molecular signatures between RMEL3 knockdown and BRAF suppression also highlights the association of RMEL3 with BRAF. Common alterations are the upregulation of FOXD3 transcription factor [11]; WNT5A [12]; JUN, STAT3 [13]; fibronectin [14]; and other molecules involved in energy metabolism [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Shared molecular signatures between RMEL3 knockdown and BRAF suppression also highlights the association of RMEL3 with BRAF. Common alterations are the upregulation of FOXD3 transcription factor [11]; WNT5A [12]; JUN, STAT3 [13]; fibronectin [14]; and other molecules involved in energy metabolism [15]. …”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment plays a key role in these adaptive responses to targeted inhibitors. For example, stromal fibroblasts may be subverted to phenotypically distinct CAFs, which promote supportive conditions for cancer cell growth through the production of soluble growth factors and the extracellular matrix (13)(14)(15)(16), induction of angiogenesis, and recruitment of inflammatory cells (14). The extent to which stromally derived factors are required for resistance to targeted inhibitors remains to be fully understood.…”
mentioning
confidence: 99%
“…Further evidence for melanoma cells experiencing an EMT-like switch following BRAF inhibitor treatment came from proteomic studies [64]. It was found that acute treatment with the BRAF inhibitor vemurafenib led to an increase in EMT associated proteins including FAK, integrin α5β1, vimentin and fibronectin [64].…”
Section: Phenotypic Adaptation As a Mediator Of Drug Resistancementioning
confidence: 99%
“…It was found that acute treatment with the BRAF inhibitor vemurafenib led to an increase in EMT associated proteins including FAK, integrin α5β1, vimentin and fibronectin [64]. The induction of fibronectin within the melanoma cells was important for therapeutic escape, with knockdown of either fibronectin or integrin α5β1 found to increase BRAF-inhibitor mediated apoptosis.…”
Section: Phenotypic Adaptation As a Mediator Of Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation